Nest daily survival rate of six Costa Rican urban birds - Ramírez Fernández José Daniel (2020)
The advance of urbanization in Neotropical countries has drastically changed or eliminated extensive areas of natural habitats. Despite these changes, some species breed in cities and adapt to urban conditions. Several variables, such as the type of nest, substrate, and height, as well as the distance to buildings at which nests are constructed, may affect nesting success of birds in urban habitats. Here we tested how these variables affect nest daily survival rate (DSR) of 6 bird species that constructed 3 different types of nests in a high human-density suburb of San Jos´e, Costa Rica. The first type includes platform nests built by 3 species of columbids, where at least 1 parent is always present at the nest; the second type includes cupshaped nests, where both parents can be absent from the nest simultaneously, and is represented by a single species, the Clay-colored Thrush (Turdus grayi); the third type includes closed nests built by 2 species where at least 1 parent is always present. Species with all 3 types of nests display protective behaviors. We quantified nest variables (e.g., type of nest, substrate used to construct the nest, nest height, distance to buildings). The nests differed in their DSR, with a higher nest survival for columbids (3 species; 0.969, SE 0.011), followed by Clay-colored Thrush (0.942, SE 0.009) and closed-nest species (2 species; 0.942, SE 0.028). We found that nesting substrate was the most important variable explaining the DSR in columbids, but none of the variables had a significant effect explaining the DSR in the remaining 2 nest types.